The Effects of Instructional Guidelines Based on the Tpack Framework on Promoting Being a Writer in Upper Secondary Education - Rakklang, Teerawoot; Termsinsuk, Saisunee; Jongkonklang , Sirinat (Journal for Developing the Social and Community, 2026)
Background and Aims: In the digital era, writing has become a vital tool for communication and for expressing students’ ideas, especially at the upper secondary level, a key transitional stage toward higher education and future careers. Effective instructional design for enhancing writing skills requires the integration of content knowledge (CK), pedagogical knowledge (PK), and technological knowledge (TK). The TPACK framework provides a foundation for developing instruction that aligns with the needs of 21st-century learners. This study aimed to (1) investigate the effects of instructional guidelines designed to promote student writing based on the TPACK framework and (2) compare the effectiveness of different guideline implementations. Methodology: This research adopted a pre-experimental design. The participants were 36 Grade 11 students from Nongnguluem Phitthayakhom School in Nakhon Ratchasima Province during the 2024 academic year. They were selected through purposive sampling and organized into 12 small groups of 3 students each. Each group implemented one of the 12 instructional guidelines developed based on the TPACK framework. Research instruments included instructional guidelines, writing assessment forms, and learning behavior observation checklists. Data were analyzed using means, standard deviations, one-way ANOVA, independent t-tests, and content analysis. Results: (1) The implemented instructional guidelines enabled students to achieve writing proficiency levels ranging from advanced to expert. Their observed learning behaviors ranged from good to excellent. While no statistically significant differences were found among the 12 guidelines, students who used electronic technology demonstrated significantly higher learning behavior scores compared to those who did not, at the .05 level. Conclusion: The research findings demonstrate that instructional guidelines incorporating the TPACK framework significantly contribute to the development of writing competencies among upper secondary school students. Furthermore, the integration of digital technology exerts a significant influence on students’ learning behaviors, which can be applied as a conceptual framework for developing writing skills in the context of 21st century learning.